Effect of recreational diving on Patagonian rocky reefs - Bravo, Gonzalo (2014)
Tourism has grown considerably in the last decades, promoting activities such as recreational SCUBA diving that may affect marine benthic communities. In Puerto Madryn, Patagonia Argentina, sub-aquatic tourism areas (STA) receive about 7,000 divers per year. Diving is concentrated on a few small rocky reefs and 50% of the dives occur in summer. In this work, we evaluated the effect of recreational diving ac- tivities on benthic communities and determined whether diving causes a press (long-term) or a pulse (short-term) response. We quanti fi ed the percentage cover of benthic organisms and compared benthic assemblage structure and composition between two sites with contrasting usage by divers, ‘ highly disturbed ’ and ‘ moderately disturbed ’ sites, and two ‘ control ’ sites with similar physical characteristics but no diving activity, twice before and after the diving peak in summer. We found differences in benthic assemblage structure (identity and relative abundance of taxa) and composition (identity only) among diving sites and controls. These differences were consistent before and after the peak of diving in summer, suggesting that recreational diving may produce a press impact on overall benthic assemblage structure and composition in these STA. At the moderately disturbed site, however, covers of speci fi c taxa, such as some key habitat-forming or highly abundant species, usually differed from those in controls only immediately after summer, after which they begun to resemble controls, suggesting a pulse impact. Thus, STA in Golfo Nuevo seem to respond differently to disturbances of diving depending on the usage of the sites. This information is necessary to develop sound management strategies in order to preserve local biodiversity.